If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 47 + -6x = 12x + 19 Reorder the terms: 47 + -6x = 19 + 12x Solving 47 + -6x = 19 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 47 + -6x + -12x = 19 + 12x + -12x Combine like terms: -6x + -12x = -18x 47 + -18x = 19 + 12x + -12x Combine like terms: 12x + -12x = 0 47 + -18x = 19 + 0 47 + -18x = 19 Add '-47' to each side of the equation. 47 + -47 + -18x = 19 + -47 Combine like terms: 47 + -47 = 0 0 + -18x = 19 + -47 -18x = 19 + -47 Combine like terms: 19 + -47 = -28 -18x = -28 Divide each side by '-18'. x = 1.555555556 Simplifying x = 1.555555556
| 7-2m=12 | | 13x-x^2=0 | | x^3+3x^2-13x-15=0 | | 4-10r=34 | | 100-2x=5x+16 | | 2(1+v)=23+5v | | 8-8x=72-22x | | 15=3n-6 | | -98-10x=7x+21 | | x^2+52x-3=0 | | 94-2x=4x+10 | | 15+4k=7 | | 5x^2-20x-45=0 | | 7p+6=6p+10 | | 6x+17=13x-39 | | x^6+x^4-32=0 | | 135+13x=25677532 | | -4x-46=6(x+9) | | 0.5x-2=22 | | 4(6-x)+7x=0 | | z-3+4=-1 | | -9(-8x-4)-7=2x+29 | | 5x^2-20x+5=50 | | 37=-3+5(x+6) | | -5n-8(1+7n)=-8 | | x^2-12x+36=2x^2+23 | | 18x^2+3x= | | 117-6x=21x+18 | | 6-8x=150-36x | | 1x+25,5*5+2=50 | | 4x+5=-47-9x | | 5a=100 |